PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA GURU DI SMP NEGERI 5 SURABAYA - Ary Muhammad Riyadi; Fauzie Senoaji; Andi Wardhana; Dina Novita (PROCEEDING UMSURABAYA, 2022)
In carrying out programs, every organization is always directed to be efficient to achieve company goals. One of the strategies is to improve employee performance. Employee performance will be carried out well if followed by the quality of human resources in which motivation and discipline factors will significantly affect the performance of employees.       This research aims to determine and analyze the effect of motivation and work discipline partially or simultaneously on teacher performance. This research uses a quantitative approach. The independent variables are motivation and work discipline, while the dependent variable is teacher performance. The data are analyzed using multiple linear regression with the F test and t-test. The results of the analysis and hypothesis testing can explain that motivation and work discipline simultaneously impact the performance of teachers at SMP Negeri 5 Surabaya, as proven by the results of statistical analysis using SPSS 26. The t-count is greater than the t-table. The research result shows that motivation and work discipline affect teachers' performance, respectively, with a value of 0.278 and 0.605, which means that the effect of the motivation and work discipline variable on teacher performance is 27, 8%, and 60.5%. By these results, the impact of work discipline on teacher performance is more significant than the effect of motivation on teacher performance. Moreover, stimulation and work field simultaneously impact teacher performance with an F-count value of 11.110 > F-table of > 1.68.Keywords: Motivation, Work Discipline, Teacher Performance.